EFFECTIVE TEACHING FOR NEW TERTIARY STUDENTS - Kitching, Chris (PEOPLE: International Journal of Social Sciences, 2015)
Students commencing tertiary studies may be casualties of their schooling and their underachievement in secondary education precludes tertiary success. Therefore, it seems desirable to involve them in collaborative and cooperative learning to better prepare them for skills demanded in the 21st century workplace. A more effective approach has the aim for students to become active, reflective, independent and collaborative learners. In developing strategies for increasing learning involvement, a key factor is the extent to which these strategies are compatible with their own expectations and preferences. Whilst ambitious it is worthwhile for university teachers to focus on how gaps between students’ ways of learning, and the ways required to achieve quality outcomes from higher education, might be bridged. Teaching and learning requires an inclusive pedagogy because it takes a wide view of intelligence and works towards teaching and assessing students using their own strengths and not be marginalised by having to focus on traditional ways of learning. This is important given the increased diversity of university students. As educators we need to find ways of discovering what our students know that is relevant to the high-level intellectual studies of university. One of the most significant changes and impacts on teaching and learning has been the universal availability of a range of information and communication technologies (ICT). This impacts on the approaches adopted by teachers and the use of technology to enhance learning.